إشكالات التنفيذ في منازعات الشهر العقاري - درويش, ماجدة (جامعة الوادي University of Eloued, 2017)
نجم عن تطبيق نظام الشهر العيني في الجزائر عدة منازعات يلجأ معها المتضرر للجهة القضائية المختصة لاستصدار حكم قضائي ينصفه، و يكون الأثر المنتج للحكم إلا بتمام تنفيذه، إلا أنه قد تطرأ إشكالات أثناء تنفيذ الأحكام القضائية الفاصلة في منازعات الشهر العقاري. إذا كانت إشكالات تنفيذ الأحكام القضائية بصفة عامة تبدو هامة ، إلا أن إشكالات تنفيذ الأحكام القضائية الصادرة بمناسبة منازعات الشهر العقاري أكثر أهمية لأن تنفيذها يكون في مواجهة الإدارة لما لها من سلطة و امتيازات على الأفراد ممثلة في مصالح الحفظ العقاري، و لأن هذه الأحكام القضائية واردة على عقار لما له أهمية في تنمية الدولة، من أهم أهداف الدراسة تسليط الضوء على أهم الإشكالات المؤدية إلى عدم التنفيذ الكلي أو الجزئي و محاولة إبراز الثغرات القانونية المؤدية لذلك. تم طرح الإشكال حول طبيعة و خصوصية الإشكالات التي تعترض تنفيذ الأحكام القضائية في مواجهة مصالح الحفظ العقاري؛ و بناء عليها قسمنا الدراسة لفصلين ،الفصل الأول يتعلق بإشكالات التنفيذ القانونية إذ حللنا بالدراسة إشكالات التنفيذ المثارة عن تطبيق قواعد قانون الإجراءات المدنية و الإدارية و الإشكالات المرتبطة بقانون الشهر العقاري ؛ أما الفصل الثاني يتعلق بإشكالات التنفيذ المادية ، و التي قسمت لإشكالات جوهرية و أخرى ثانوية ، فأما الجوهرية تتمثل في امتناع إدارة الشهر العقاري عن التنفيذ و استحالة التنفيذ لارتباط قانون الشهر العقاري بالأنظمة و النصوص القانونية. أما الثانوية منها تتمثل في غموض الأحكام القضائية و الأخطاء الواردة فيها إلى جانب الإشكالات التقنية و الفنية. من خلال الدراسة ظهر بأن إشكالات التنفيذ في منازعات الشهر العقاري لها طبيعتها الخاصة المختلفة عن إشكالات التنفيذ الواردة في قانون الإجراءات المدنية و الإدارية. و عليه نقترح إناطة مهمة المحافظ العقاري لقاضي عقاري ، و إنشاء قضاء عقاري متخصص و تنظيم ملتقيات و ندوات في هذا الصدد. As a result of the application of the month-in-kind system in Algeria, there are several disputes with which the injured party resorted to the competent judicial authority to obtain a judicial ruling that is fair and the productive effect of the judgment is only the full implementation. However, there may be problems during the execution of the judgments in the real estate disputes. If the problems of implementation of judicial decisions in general seem important, however, the problems of implementation of judicial decisions issued on the occasion of the disputes of the real estate month is more important because their implementation is in the face of the administration because of its authority and privileges to individuals represented in the interests of real estate conservation, on the property because of its importance in the development of the State, Of the most important objectives of the study highlight the most important problems leading to the lack of total or partial implementation and attempt to highlight legal loopholes leading to it. The first issue concerns the problems of legal implementation as we analyzed the problems of implementation arising from the application of the rules of civil and administrative law and the problems associated with the law The real estate month; the second chapter relates to the problems of physical and real implementation, which was divided into other fundamental and secondary problems, either the essence is the failure of the management of the month of real estate implementation and impossibility of implementation of the law of the month of real estate And of legal texts. The secondary ones is the ambiguity of judicial decisions and errors contained therein, as well as technical and technical problems. Through the study that appeared problematic implementation in real estate disputes month its own different nature from problematic implementation contained in the Code of Civil Procedure and the administrative. And we propose the assignment of important real estate real estate portfolios judge, and the establishment of a real estate specialist and spend organizing seminars and symposia in this regard.
قانون عقاري
Keywords: إشكالات تنفيذ الأحكام القضائية الفاصلة في منازعات الشهر العقاري-إشكالات التنفيذ القانونية-إشكالات التنفيذ المادية; Problems of legal implementation Problems of physical implementation